2014
DOI: 10.1007/s40620-014-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between calcium kidney stones, arterial stiffness and bone density: unraveling the stone-bone-vessel liaison

Abstract: Our study confirms that stone formers have increased arterial stiffness and reduced bone density. Abnormal arterial stiffness appears to be independent of reduced bone density and may explain the higher CV risk observed in stone formers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
(26 reference statements)
3
33
0
1
Order By: Relevance
“…First, there is strong evidence that urolithiasis is associated with several systemic diseases, including metabolic syndrome, hypertension, diabetes mellitus, increased arterial stiffness and subclinical atherosclerosis. 4,12,13 Our study also demonstrated that the urolithiasis cohort was more vulnerable to hypertension, hyperlipidaemia and diabetes mellitus. The relatively higher prevalence of these cardiovascular risk factors in patients with urolithiasis may contribute to the higher risk of both ischaemic and haemorrhagic stroke in this population.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…First, there is strong evidence that urolithiasis is associated with several systemic diseases, including metabolic syndrome, hypertension, diabetes mellitus, increased arterial stiffness and subclinical atherosclerosis. 4,12,13 Our study also demonstrated that the urolithiasis cohort was more vulnerable to hypertension, hyperlipidaemia and diabetes mellitus. The relatively higher prevalence of these cardiovascular risk factors in patients with urolithiasis may contribute to the higher risk of both ischaemic and haemorrhagic stroke in this population.…”
Section: Discussionsupporting
confidence: 64%
“…Several theories can be discussed. First, there is strong evidence that urolithiasis is associated with several systemic diseases, including metabolic syndrome, hypertension, diabetes mellitus, increased arterial stiffness and subclinical atherosclerosis . Our study also demonstrated that the urolithiasis cohort was more vulnerable to hypertension, hyperlipidaemia and diabetes mellitus.…”
Section: Discussionsupporting
confidence: 62%
“…19 Arterial stiffness, which was assessed by carotid-radial pulse wave velocity, carotid-femoral pulse wave velocity and the augmentation index, has been associated with early atherosclerosis. 20 The group noted that such a process also occurs elsewhere, eg in central elastic arteries and peripheral muscular arteries, adding support to the view that this is a systemic phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Fabris et al went on to confirm the possible relationship between nephrolithiasis and premature atherosclerosis. In their study, a higher pulse wave velocity in KSFs was demonstrated, suggesting an increased stiffness of small arteries, presumably as a consequence of vascular calcification (VC) (6).…”
Section: Introductionmentioning
confidence: 88%